Implementation of Restorative Justice in Surakarta District Court - Abdul Fattaah; Sutrisno Sutrisno; Jaka Susila (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2024)
The postponement of the Decree of the Director General of Badilum Number 1691/DJU/SK/PS.00/12/2020 concerning Guidelines for the Implementation of Restorative Justice in the General Court Environment by Letter Number 1209/DJU/PS.00/11/2021 until the Supreme Court regulations regarding guidelines for justice come into force Restorative raises problems, namely what the Surakarta District Court's policy is regarding the implementation of justice. This field research type uses interview and documentation data collection methods and data analysis techniques using the interactive model from Miles and Huberman. The research results show that in their authority to examine and adjudicate cases, judges must pay attention to contextual matters in resolving cases using a restorative justice approach, which resolves criminal cases by involving perpetrators, victims, and other parties who work together to find a satisfactory solution. fair by emphasizing restoration to the original state, not retaliation. Resolving cases using restorative justice, lack of support and cooperation between institutions, and the justice system not regulating much about victims' rights.